Students’ Learning During Coronavirus Outbreak in Malaysian Higher Learning Institution - Steven Eric Krauss; Ismi Arif Ismail; Habibah Ab Jalil; Abd Rahman Ahmad; Mohd Shahir Shamsir Omar (Communications of International Proceedings, 2020)
The purpose of this paper is to highlight the potential impact of the outbreak on students learning in one of the public universities in Malaysia, providing greater clarity on what kinds of technological and psychosocial support are needed to address their students’ needs. A set of online questionnaires distributed to students through social media, using the online platform Survey. Data were collected during the early stages of the COVID-19 Mandatory Control Order (MCO) period from 26th March to 3rd April 2020. The survey included 1,450 undergraduate and postgraduate students from different faculties within one university in Malaysia. Results indicated that some of the challenges faced by students include difficulty undertaking online learning due to poor or unreliable internet connectivity, unfamiliarity with online learning mode, and difficulty completing online learning tasks assigned by lecturers. In light of the survey findings, recommendations are made for administrators, lecturers, and students to address student well-being and continuity of learning during the coronavirus pandemic situation
Keywords: Higher Learning Institutions; student learning; learning resources; COVID-19